The alerting expression of microRNA-411 predicts clinical prognosis and regulates tumor progression of glioblastoma. Issue 1 (1st January 2021) - Fan, Weihua; Yu, Xia; Li, Kunrong; Zhu, Mingtao
ABSTRACT: Glioblastoma is a malignant intracranial tumor with indispensable growth. Identification of biomarkers associated with the progression of tumors could benefit the clinical therapy of and improve patient's survival. miR-411 has been reported to play a role in other cancers, while its function in glioblastoma has been explored in the present study. The expression of miR-411 was evaluated in glioblastoma tissues (collected from 108 glioblastoma patients) and cells by polymerase chain reaction. The clinical significance of miR-411 was estimated with a series of statistical analyses. The biological function of miR-411 in the cellular processes of glioblastoma was assessed by cell counting kit 8 and Transwell assay. The expression of miR-411 was significantly reduced in glioblastoma, which was associated with the Karnofsky Performance Score (KPS) and Isocitrate dehydrogenase 1 (IDH1) status of patients. miR-411 was identified as an independent prognostic indicator that correlated with the poor prognosis of patients. miR-411 suppressed the growth, migration, and invasion of glioblastoma cells via modulating signal transducer and activator of transcription 3 (STAT3). miR-411 participated in the development of glioblastoma and function as a prognostic biomarker. miR-411 functions as a tumor suppressor, which provides a novel potential therapeutic target for glioblastoma.